Studies of Some Antifungal Agents - Singh, C.P.; Kumar Prajapati, Sahedev (Asian Journal of Chemistry, 2010)
A series of N´-(4-pyridoyl)-3-methyl-4-(substituted arylidene)-2-pyrazolin-5-ones have been synthesised to study their antifungal activity. All the compounds have been screened for their antifungal activity against the rice blast pathogen Pyricularia oryzae and brown leaf spot pathogen Helminthosporium oryzae and found to be antifungal.